PENGGUNAAN AGREGAT SUB STANDAR DAN AGREGAT LOKAL UNTUK CAMPURAN BERASPAL - Leksminingsih Leksminingsih (Jurnal Jalan-Jembatan, 2005)
The study using sub standard aggregate and local agregate for asphalt mixed, it covers mixed design asphalt using five aggregates, there are : standard aggregate, sub standard aggregate that not fulfill the specification, marble aggregate, slag aggregate and limestone aggregate. The result of the mixed asphalt there are, limestone aggregate had a Marshall stability more higher than a standard mixed, is 1820 kg, when slag aggregate nave dynamic stability more higher than standard, is 2100 passing/minute, and permanent deformation also lower than a standard. The test of modulusresulient between slag and standard aggreate are similar, have a same number, but limestoe aggregate have a lower modulus on 25oC, is 41% lower than a standard mixed. The aggregate that have a bad performance is marble aggregate, that have a low Marshall stability is 16,7%, deformation permanent increase 18% and dynamic stability is lowe 52% than standard mixed, when the sub standard aggregate have a lower retain Marshall stability < 75% to original stability. To prove this result, it should be make an application on field, to know the similar performance on laboratory.